Pengaruh Penggunaan Umpan Balik (Feedback) Terhadap Hasil Belajar Siswa Dalam Mata Pelajaran Biologi - Santosa, Tomi Apra; Lufri, Lufri; Razak, Abdul; sastria, Emayulia; Zulyusri, Zulyusri (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2021)
This study aims to determine the effect of user feedback on student learning outcomes in fiqh subjects. This research is a quasi experiment. Data obtained through tests. The data analysis is the t test. Before applying the hypothesis, a prerequisite test is carried out. The results showed that students without using the feedback technique the average student was 72.86 with a standard deviation of 6.712 and a variance of 45.055 and the scores of students who used the feedback technique were obtained from the postest score with an average score of 82.50 with a standard deviation of 7.532 and variant of 56,751. The hypothesis obtained is T count = 3.838> T table = 2.145, the effect of the use of feedback on student learning outcomes in biology learning in class XI IPA MAN 3 Kerinci. Learning with feedback techniques is suitable for use in public schools..